2009
DOI: 10.1042/cs20080647
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7), an alternative metabolite of the renin–angiotensin system, is up-regulated in human liver disease and has antifibrotic activity in the bile-duct-ligated rat

Abstract: Ang-(1-7) (angiotensin-1-7), a peptide product of the recently described ACE (angiotensin-converting enzyme) homologue ACE2, opposes the harmful actions of AngII (angiotensin II) in cardiovascular tissues, but its role in liver disease is unknown. The aim of the present study was to assess plasma levels of Ang-(1-7) in human liver disease and determine its effects in experimental liver fibrosis. Angiotensin peptide levels were measured in cirrhotic and non-cirrhotic patients with hepatitis C. The effects of An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
127
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(141 citation statements)
references
References 50 publications
13
127
1
Order By: Relevance
“…This result suggests that the local RAS is activated in BDL rats and that inhibition of the RAS with telmisartan could inhibit the progression of fibrosis. These findings are consistent with previous reports in which the ACE2/Ang (1-7)-Mas axis plays a key role during liver fibrosis [6,7] .…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This result suggests that the local RAS is activated in BDL rats and that inhibition of the RAS with telmisartan could inhibit the progression of fibrosis. These findings are consistent with previous reports in which the ACE2/Ang (1-7)-Mas axis plays a key role during liver fibrosis [6,7] .…”
Section: Discussionsupporting
confidence: 83%
“…This observation is consistent with other studies in which ACE2 upregulation in fibrotic livers has been observed [6,7] . MAS expression levels closely paralleled the elevated ACE2 expression levels in rat liver, suggesting that increased ACE2 expression levels may favor the formation of Ang (1-7) and further amplify MAS expression levels.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations